2020
DOI: 10.1186/s13063-020-04283-5
|View full text |Cite
|
Sign up to set email alerts
|

ATLANTIS: a randomised multi-arm phase II biomarker-directed umbrella screening trial of maintenance targeted therapy after chemotherapy in patients with advanced or metastatic urothelial cancer

Abstract: Background: Metastatic urothelial cancer (UC) is the eighth most common cause of cancer death in the UK. Standard first-line treatment, for most patients, is cytotoxic chemotherapy. Although UC is initially sensitive to chemotherapy, relapse is almost inevitable and outcomes are poor; median overall survival is 8 months. Therefore, there is an urgent need for novel therapies to improve outcomes for this patient group. Methods: ATLANTIS is a randomised phase II umbrella-design screening trial of maintenance the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…AFFILIATIONS 1 Southampton Experimental Cancer Medicine Centre, University of Southampton, Southampton, United Kingdom 2 University of Sheffield and Sheffield Teaching Hospitals, Sheffield, United Kingdom 3 CRUK Glasgow Clinical Trials Unit, University of Glasgow, Glasgow, United Kingdom 4 The Christie NHS Foundation Trust, Manchester, United Kingdom 5 Velindre Cancer Centre, Cardiff, United Kingdom 6 Northern Centre for Cancer Care, Newcastle upon Tyne, United Kingdom 7 Portsmouth Hospitals NHS Trust, Portsmouth, United Kingdom 8 Leicester Royal Infirmary NHS Trust, Leicester, United Kingdom 9…”
Section: Corresponding Authormentioning
confidence: 99%
See 2 more Smart Citations
“…AFFILIATIONS 1 Southampton Experimental Cancer Medicine Centre, University of Southampton, Southampton, United Kingdom 2 University of Sheffield and Sheffield Teaching Hospitals, Sheffield, United Kingdom 3 CRUK Glasgow Clinical Trials Unit, University of Glasgow, Glasgow, United Kingdom 4 The Christie NHS Foundation Trust, Manchester, United Kingdom 5 Velindre Cancer Centre, Cardiff, United Kingdom 6 Northern Centre for Cancer Care, Newcastle upon Tyne, United Kingdom 7 Portsmouth Hospitals NHS Trust, Portsmouth, United Kingdom 8 Leicester Royal Infirmary NHS Trust, Leicester, United Kingdom 9…”
Section: Corresponding Authormentioning
confidence: 99%
“… 4 , 6 , 7 However, maintaining clinical benefit from first-line chemotherapy represents an attractive strategy to improve outcomes. 6 , 8 Avelumab maintenance immunotherapy, following first-line chemotherapy, improves survival and represents a new standard of care. 6 However, only a minority of patients appear to benefit from immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly allowed adaptation was futility/efficacy monitoring (60.0%, 9/15). Other adaptive features observed were adaptive randomization (20.0%, 3/15) ( 38 , 39 ), sample size re-estimation (6.7%, 1/15) ( 40 ), addition of new arms (13.3%, 2/15) ( 23 , 41 ), and a two-stage design to terminate ineffective treatments in stage I (20%, 3/15) ( 23 , 42 , 43 ).…”
Section: Characteristics Of Conducted Umbrella Trialsmentioning
confidence: 99%
“…In this study, BRCAness phenotype was retrospectively evaluated: HRR alterations were found in 44.7% of patients, illustrating platinum sensitivity of mUC with DDR deficiency. In contrast, the Atlantis trial is a biomarker-directed, multi-arm phase II study, in maintenance setting for mUC after platinum-based chemotherapy response or stable disease [ 12 , 13 ]. Results from the Atlantis rucaparib arm in DDR-selected mUC were recently presented: maintenance rucaparib was associated with promising benefit as compared to placebo (median PFS 35 versus 15 weeks respectively, HR 0.53, 80% CI 0.30–092; p = 0.07).…”
Section: Introductionmentioning
confidence: 99%